The Impact of Self-Efficacy on Performance Employee: Study of Literature - Rajendra Dwi Maheswara; Nuha Aliyah; Fatahillah Ayatulloh Khomeini (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
Self-efficacy is an individual's self-confidence or belief in their ability to do something, produce something, organize, achieve their goals, and also implement actions to realize certain skills. A person's self-efficacy will usually influence the individual in determining an action or decision. Where the action is carried out to achieve a goal or several things or possibilities that will be present in the future. The purpose of this research is to find out the effect of self-efficacy on employee performance. The research method used is qualitative with a literacy review approach through the selection of keywords namely